Effects of driverless vehicles: Comparing sim ulations to get a broader picture - Pernestål, Anna; Kristoffersson, Ida (European Journal of Transport and Infrastructure Research, 2019)
Driverless vehicles have the potential to significantly affect the transport system, society, and environment. However, there are still many unanswered questions regarding what the development will look like, and there are several contradictory forces. This paper addresses the effects of driverless vehicles by combining the results from 26 simulation studies. Each simulation study focuses on a particular case, e.g. a certain mobility concept or geographical region. By combining and analysing the results from the 26 simulation studies, an overall picture of the effects of driverless vehicles is presented. In the paper, the following perspectives are considered: what types of application of driverless vehicles have been studied in literature; what effects these simulation studies predict; and what research gaps still exist related to the effects of driverless vehicles. The analysis shows that it is primarily driverless taxi applications in urban areas that have been studied. Some parameters, such as trip cost and waiting time, show small variations between the simulation studies. Other parameters, such as vehicle kilometres travelled (VKT), show larger variations and depend heavily on the assumptions concerning value of time and level of sharing. To increase the understanding of system level effects of driverless vehicles, simulations of more complex applications and aspects such as land use, congestion and energy consumption are considered.